Smallholder dairy methodology: Draft methodology for quantification of GHG emission reductions from improved management in smallholder dairy production systems using a standardized baseline - Food and Agriculture Organization of the United Nations; International Livestock Research Institute (Food and Agriculture Organization of the United Nations, 2016)
This methodology presents requirements for development and assessment of a standardized baseline for quantification of greenhouse gas (GHG) emission reductions in smallholder dairy systems. It also includes guidance for quantification of baseline GHG emissions from dairy production in a defined geographical area within a country, for quantification of with-project GHG emissions, leakage, and net emission reductions due to project implementation. The general approach outlined in the methodology is based on the following key elements. A standardized baseline for the project region is set on the basis of a baseline survey, which establishes a statistically robust relationship between milk yields and the GHG intensity of milk production measured as kg CO2 eq. per kg fat and protein corrected milk (FPCM).